The attitude of Muslims and Non-Muslims towards Islamic Products and Services in the UK - Atsede Woldie; Md. Mahit Hossain (Universitas Trisakti, 2011)
Islamic banks are the fastest growing banks in the world. Governments around the world are passing bills to enable the smooth operation of Islamic banking and finance as part of their financial systems. This paper explored the awareness. attitude, and their bank selection criteria of both •uslims and Non-Muslims in the UK. Thc results showed that although the Muslims knew the meaning of fundamental terms in Islam, non-Muslims arc totally unaware about basic Islamic financial terms and principles. They also perceived that products were only for Muslims people only. The study indicated that more than 46 percent of Muslims respondents perceive that religion is the only reason to motivate people to deposit money with Islamic banks.